PENGARUH INFESTASI NEMATODA Pratylenchus TERHADAP PERTUMBUHAN TANAMAN NENAS [Ananas comosus (L.) Merr.] - I Gede Swibawa , Irma Amaliah, Titik Nur Aeny (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2001)
Pratylenchus is an important parasitic nematode on pineapples in the world. This plant parasitic nematodes may cause severe damages on roots, resulted in retarded plant growth. The experiment consisted of four Pratylenchus population levels per plant with 4 replications. The experiment was conducted on June to September 1999, on PT. Great Giant Pineapple Company (GGPC) in Central Lampung District. The aim of the research was to study the nematode population effects on root damages and plant growth. The result showed that smooth cayenne variety was a favorable host of Pratylenchus. Rapid rate of nematode population occurred in three months. The root damage of infested plant with as much as 100 - 300 nematodes per plant was up to 20.39 - 31.72 percent and caused canopy wet weight was a half lower than those untreated plant.